Type 3 Immunity during Clostridioides difficile Infection: Too Much of a Good Thing? - Saleh, Mahmoud M. (Infect Immun, 2019)
Clostridioides (formerly known as Clostridium) difficile is the leading cause of hospital-acquired gastrointestinal infections in the United States and one of three urgent health care threats identified by the Centers for Disease Control and Prevention. C. difficile disease is mediated by the production of toxins that disrupt the epithelial barrier and cause a robust host inflammatory response. Studies in humans as well as animal models of disease have shown that the type of immune response generated against the infection dictates the outcome of disease, often irrespective of bacterial burden. Much of the focus on immunity during C. difficile infection (CDI) has been on type 3 immunity because of the established role for this arm of the immune system in other gastrointestinal inflammatory conditions such as inflammatory bowel disease (IBD). For example, interleukin-22 (IL-22) production by group 3 innate lymphoid cells (ILC3s) protects against pathobionts translocating across the epithelium during CDI. On the other hand, interleukin-17 (IL-17) production by Th17 cells increases CDI-associated mortality. Additionally, neutropenia has been associated with increased susceptibility to CDI in humans, but increased neutrophilia in mouse models correlates with host pathology. Taking the data together, these findings suggest dual roles for type 3 immune responses during infection. Here, we review the complex role of type 3 immunity during CDI and delineate what is known about innate and adaptive cellular immunity as well as the downstream effector cytokines known to be important during this infection.